Chalcone derivatives as potential antifungal agents: Synthesis, and antifungal activity - Deepa Gupta; D K Jain (Wolters Kluwer Medknow Publications, 2015)
Much research has been carried out with the aim to discover the therapeutic values of chalcone derivatives. Chalcones possess wide range of pharmacological activity such as antibacterial, antimalarial, antiprotozoal, antitubercular, anticancer, and antifungal agents etc. The presence of reactive α,β-unsaturated keto group in chalcones is found to be responsible for their biological activity. The rapid developments of resistance to antifungal agents, led to design, and synthesize the new antifungal agents. The derivatives of chalcones were prepared using Claisen-Schmidt condensation scheme with appropriate tetralone and aldehyde derivatives. Ten derivatives were synthesized and were biologically screened for antifungal activity. The newly synthesized derivatives of chalcone showed antifungal activity against fungal species, Microsporum gypseum. The results so obtained were superior or comparable to ketoconazole. It was observed that none of the compounds tested showed positive results for fungi Candida albicans nor against fungi Aspergillus niger. Chalcone derivatives showed inhibitory effect against M. gypseum species of fungus. It was found that among the chalcone derivatives so synthesized, two of them, that is, 4-chloro derivative, and unsubstituted derivative of chalcone showed antifungal activity superior to ketoconazole. Thus, these can be the potential new molecule as antifungal agent.